2004
DOI: 10.1183/09031936.04.00040304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise training on cardiac baroreflex sensitivity in patients with COPD

Abstract: Influence of exercise training on cardiac baroreflex sensitivity in patients with COPD. F. Costes, F. Roche, V. Pichot, J.M. Vergnon, M. Garet, J-C. Barthelemy. #ERS Journals Ltd 2004. ABSTRACT: Decreased spontaneous cardiac baroreflex sensitivity (BRS), which could lead to the onset of cardiovascular events, has been demonstrated in chronic obstructive pulmonary disease patients. This study evaluates the effects of an exercise training programme on BRS.Twenty-one chronic obstructive pulmonary disease patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 32 publications
4
49
1
2
Order By: Relevance
“…These range from a reduction in heart rate variability [25][26][27], a reduction in respiratory sinus arrhythmia [27] and a reduction in baroreflex sensitivity [28,29], together with a direct increase in muscle sympathetic nerve activity [30,31]. In the present study, the COPD patients had depressed baroreflex sensitivity, regardless of their history of smoking and of the current therapy.…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 48%
“…These range from a reduction in heart rate variability [25][26][27], a reduction in respiratory sinus arrhythmia [27] and a reduction in baroreflex sensitivity [28,29], together with a direct increase in muscle sympathetic nerve activity [30,31]. In the present study, the COPD patients had depressed baroreflex sensitivity, regardless of their history of smoking and of the current therapy.…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 48%
“…Several other studies also concluded that regular physical activity increases vagal influence on the HR and BRS, while the sympathetic tone may be decreased. 8,[11][12][13]17,19,25,27,32,34 However, Iellamo et al 25 found a reversal of these effects after a period of training at 100% training load. Very intensive training shifted the CV autonomic modulation from PNS toward SNS predominance.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,[10][11][12][13]15,17,18,[19][20][21]25,27,[30][31][32][34][35][36]38,39,45,47 The results of 10 articles on ANS response measured during exercise are shown in Table I. Some authors expressed concern about the measurement of spectral analysis of HRV during exercise, while others reported increases (↑), decreases (↓) and no changes in variability indicators (↔) of sympathetic (SNS) and parasympathetic (PNS) influence.…”
Section: Resultsmentioning
confidence: 99%
“…2,5,6 Consequently, autonomic function in patients with COPD has received a considerable amount of attention in the literature. [2][3][4][5][6][7][9][10][11] The autonomic nervous system controls and regulates the internal physiology of the body and plays a very important role in the pathophysiology of COPD. It consists of 2 branches (sympathetic and parasympathetic), both of which exert antagonistic effects on most bodily functions and also contribute to homeostasis in the body.…”
Section: Introductionmentioning
confidence: 99%